Snapping Knee Caused by Medial Meniscal Cyst - Tsuyoshi Ohishi; Daisuke Suzuki; Kazufumi Yamamoto; Tomohiro Banno; Hiroki Ushirozako; Yoichi Koide; Yukihiro Matsuyama (Case Reports in Orthopedics)
Snapping phenomenon around the medial aspect of the knee is rare. We present this case of snapping knee caused by the sartorius muscle over a large medial meniscal cyst in a 66-year-old female. Magnetic resonance images demonstrated a large medial meniscal cyst with a horizontal tear of the medial meniscus. Arthroscopic cyst decompression with limited meniscectomy resulted in the disappearance of snapping, and no recurrence of the cyst was observed during a 2-year follow-up period.